Social policy and EU polity-building through crises and beyond - Kyriazi, Anna; Miró, Joan 1992-; Natili, Marcello 1984-; Ronchi, Stefano 1974- (Routledge, Taylor & Francis Group, 2025)
This volume sets out to explain the conditions that have favoured the expansion of the European social dimension during the turbulent decade of 2010-20, when Europe was confronting strong countervailing pressures, including the euro crisis, the refugee crisis and the COVID-19 pandemic. The study begins by diagnosing a widespread, although slow-burning, crisis across the European Union (EU) resulting from the cumulation of social problems and the systemic tension between EU market integration on the one hand and nationally bounded welfare states and the other. Eight in-depth case studies analyse the political dynamics behind a variety of EU social initiatives aimed at addressing the consequences of free movement of workers, youth unemployment, poverty, eroding wages, environment and climate change, and the COVID-19 pandemic. To identify the specific drivers of EU social policymaking empirically, the authors have reconstructed the struggles over concrete policy proposals as they unfolded in the European multilevel setting. The volume introduces a novel analytical framework for interpreting the transformation of the EU social dimension in times of crisis, when some degree of social co-ordination becomes crucial to bond deeply different (welfare) states together. This in-depth study offers an invaluable analysis for researchers, academics and professionals interested in the functioning of the European polity. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license
Keywords: Europäische Union; Sozialgeschichte 2010-2020; Sozialpolitik; European Union; Social policy; EU/EC Policy